Studies on the antibacterial activity of the antimicrobial peptide Mastoparan X against methicillin-resistant Staphylococcus aureus - Zhangping Lu; Xiaofang Liang; Wenbo Deng; Qianqian Liu; Yulin Wang; Meng Liu; Fugui Lin; Zhihong Liu; Yu Zhang; Wenjie Wang; Yingying Sun; Yaozhou Wu; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) poses a serious threat to the public health system due to its multi-drug resistance and strong biofilm-forming ability. Here, we explored the possible inhibitory mechanism of an antimicrobial peptide, Mastoparan X, against MRSAMethodsMinimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Mastoparan X against MRSA USA300 were determined by microbroth dilution method. The antibacterial activity of Mastoparan X against USA300 was then evaluated by time-growth curves, membrane fluidity, reactive oxygen species(ROS), flow cytometry, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). In addition, the inhibitory and scavenging effects of Mastoparan X on USA300 biofilm were evaluated using crystal violet staining. Finally, gene expression changes in USA300 after treatment with Mastoparan X were analyzed by transcriptomics and verified by RT-qPCR.ResultsThe MIC and MBC of Mastoparan X on USA300 were 32 μg/mL and 64 μg/mL, respectively. SEM observation showed significant changes in cell morphology after Mastoparan X treatment. Flow cytometry confirmed that Mastoparan X promoted the apoptosis of MRSA cells. In addition, Mastoparan X inhibited the formation of MRSA biofilm while destroying the mature bioepithelia already formed. Transcriptomic analysis showed that 851 genes were significantly altered and ABC transport protein, amino acid biosynthesis, glycolysis and tricarboxylic acid (TCA) cycle were inhibited after 16μg/mL Mastoparan X treatment.ConclusionOur study demonstrated that Mastoparan X has potent bactericidal activity against MRSA and is expected to provide new potential peptides for the clinical treatment of MRSA.